2011
DOI: 10.1186/1471-2164-12-206
|View full text |Cite
|
Sign up to set email alerts
|

Identification of ovule transcripts from the Apospory-Specific Genomic Region (ASGR)-carrier chromosome

Abstract: BackgroundApomixis, asexual seed production in plants, holds great potential for agriculture as a means to fix hybrid vigor. Apospory is a form of apomixis where the embryo develops from an unreduced egg that is derived from a somatic nucellar cell, the aposporous initial, via mitosis. Understanding the molecular mechanism regulating aposporous initial specification will be a critical step toward elucidation of apomixis and also provide insight into developmental regulation and downstream signaling that result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 49 publications
1
21
0
Order By: Relevance
“…In the case of Tripsacum , the current evidence suggests the presence of barriers in the transfer of apomixis to maize (Leblanc et al 2009). The greatest progress has been made with the introgression of apomixis into pearl millet from Pennisetum , where a single alien chromosome persists in the most advanced apomictic lines (Singh et al 2010; Zeng et al 2011). In the sexual model plant Arabidopsis , for each element of apomixis identified by mutation so far, the penetrance was shown to be generally low and the related candidate genes were never found to be associated with any feature of apomixis in natural apomicts.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of Tripsacum , the current evidence suggests the presence of barriers in the transfer of apomixis to maize (Leblanc et al 2009). The greatest progress has been made with the introgression of apomixis into pearl millet from Pennisetum , where a single alien chromosome persists in the most advanced apomictic lines (Singh et al 2010; Zeng et al 2011). In the sexual model plant Arabidopsis , for each element of apomixis identified by mutation so far, the penetrance was shown to be generally low and the related candidate genes were never found to be associated with any feature of apomixis in natural apomicts.…”
Section: Discussionmentioning
confidence: 99%
“…These read lengths enable effective assembly of sequence data even in the absence of a reference genome sequence and have spurred a recent flurry of transcriptome projects in non-model organisms (e.g. Vera et al 2008;Meyer et al 2009;Schwartz et al 2010), including numerous angiosperms (Novaes et al 2008;Alagna et al 2009;Barakat et al 2009;Bellin et al 2009;Soltis et al 2009;Wang et al 2009;Buggs et al 2010;Peng et al 2010;Sun et al 2010;Zeng et al 2010Zeng et al , 2011Angeloni et al 2011;Bai et al 2011;Blanca et al 2011;Dutta et al 2011;Franssen et al 2011;Fu et al 2011;Kaur et al 2011;Logacheva et al 2011;Lu et al 2011;McDowell et al 2011;Portnoy et al 2011;Swarbreck et al 2011;Yang et al 2011). In this study, we report the results of using 454 sequencing to analyse a normalized cDNA library derived from a pooled sample of multiple tissue types and populations of S. vulgaris, including functional annotation of expressed gene content, marker discovery and an analysis of nucleotide diversity.…”
Section: Introductionmentioning
confidence: 99%
“…Recent transcriptome analyses of the ASGR-carrier chromosome of Pennisetum show that one transcript, which is tightly linked to the heterochromatic ASGR and has similarity to the Transposase_24 domain, is expressed in vegetative and reproductive tissues. A MADS domain-containing gene and a Lon protease present on the ASGR-carrier chromosome were also expressed only in reproductive tissues, but their cosegregation with the ASGR was not confirmed (Zeng et al, 2011). Our cytogenetic analysis of H. caespitosum C36 chromosomes indicated that the chromosomal region containing the LOA locus and associated repetitive sequences is not enriched in heterochromatic marks relative to other chromosomes, suggesting that it may also be transcriptionally active.…”
Section: Convergent Evolution Of Chromosomes Containing Apospory Locimentioning
confidence: 99%